Pengaruh Pola Asuh Orang Tua terhadap Minat Belajar Siswa Setingkat Sekolah Menengah Atas - Salsabilla, Amalia; Darmawan, Didit (YASIN, 2024)
This study aims to analyze the influence of parental parenting on students' interest in learning at the high school level in Indonesia. The role of educators is not only the responsibility of teachers at school, parents have an important role to support children's education when outside of school. Effective and efficient parenting has a great influence on students' interest in learning, at school students receive education and at home students actualize what they have received, the role of parents is important to provide the right response so that it is able to increase the motivation of students' interest in learning. The urgency of parental parenting for children, especially for high school students who are in adulthood. Thus, the form of parental attention to their children in education is not only in material form, but must be balanced with parental attention that is given directly, not only the provision of facilities that support education. But also, motivate children in learning, accompany them, ask questions, help solve problems faced and so on. This study applies a literature review method through analysis of various relevant scientific sources. The results of the study revealed that parental parenting has a real contribution to increasing students' interest in learning, especially students at the high school level. The influence of parental parenting has an important role because it can encourage the emergence of students' self-awareness in learning. Parents are expected to be able to create and maintain a supportive environment in increasing students' interest in learning in order to achieve learning with maximum results.